Examining Initial Post-Concussion Dizziness and Postural Stability as Potential Recovery Predictors. (4th January 2022) - Smulligan, Katherine; Wingerson, Mathew; Seehusen, Corrine; Wilson, Julie; Howell, David R.
Abstract : Objective: To examine the association between acute post-concussion dizziness, initial symptom severity, and postural stability with time to symptom resolution among adolescents. Background: Identifying early post-concussion symptoms and functional deficits that predict symptom resolution can guide treatment strategies. Dizziness is among the most common concussion symptoms, and existing literature investigating the association between dizziness and recovery time is mixed. Design/Methods: Participants underwent initial evaluation = 14 days post-concussion, and self-reported symptom severity using the Post-Concussion Symptom Inventory (PCSI). We used PSCI dizziness ratings to group participants: a difference between current and pre-injury dizziness ≥3 = dizzy; difference <3 = not dizzy. We evaluated postural stability using modified Balance Error Scoring System (mBESS) and tandem gait (TG). Patients were followed until symptom resolution, and our primary outcome of interest was time from concussion to symptom resolution. Using a univariable Cox proportional hazard model, we examined the association of dizziness and symptom resolution time. We then used a multivariable Cox proportional hazard model to adjust for variables that differed between groups. Results: We examined 89 participants, grouped as dizzy (n = 34; age = 14.7 ± 2.7 years; 7.1 ± 3.4 days post-injury; symptom resolution time = 40.8 ± 5.7 days) or not dizzy (n = 55; age = 14.4 ± 2.3 years; 7.2 ± 3.1 days post-injury; symptom resolution time = 23.3 ± 3.2 days). Upon univariable examination, dizziness was independently associated with symptom resolution time (HR = 0.49; 95% CI: 0.28, 0.83; p = 0.009). After adjusting for potential confounding variables (initial symptom severity, mBESS tandem stance errors, TG time, and loss of consciousness) multivariable model results indicated initial symptom severity was the only variable associated with symptom resolution time (HR = 0.98; 95% CI: 0.96, 0.997; p = 0.025). Conclusions: Total symptom severity, but not dizziness or postural stability, was significantly associated with symptom resolution time among adolescents following concussion. Individuals with moderate to severe post-concussion dizziness had higher average symptom scores indicating self-reported dizziness should be interpreted in the context of total concussion symptom burden.